MAPPING THE SOCIAL DIMENSIONS OF SCHOOL SPORTS: A BIBLIOMETRIC STUDY OF SPORTS SOCIOLOGY RESEARCH - Vurba, Multy; Fitri, Mustika; Paramitha, Sandey Tantra; Apriady, Hilmy (STKIP Singkawang, 2024)
This bibliometric study investigates the critical role of social support in school sports, emphasizing its impact on students' personal development and engagement. Drawing on a comprehensive analysis of 2,245 articles published from 2014 to 2024, this research identifies emerging trends, influential authors, and key publications in the field. Findings reveal that participation in school sports enhances not only physical fitness but also emotional, cognitive, and social skills, ultimately contributing to life satisfaction and academic success. The analysis highlights the significance of a supportive network—including family, peers, and educators—in fostering positive outcomes for young athletes. Despite the growing interest in this area, gaps in the literature regarding the longitudinal evolution of social support in school sports are evident, necessitating further exploration of its dynamics across diverse cultural contexts. The study also presents a keyword cluster analysis that delineates two primary themes: methodological approaches and participant characteristics, shedding light on prevailing research foci. This research underscores the importance of interdisciplinary collaboration among educators, policymakers, and researchers to prioritize social support within school sports frameworks, thereby enhancing the educational experience and promoting holistic development among students.